The standards of the prisoner’s rights restrictions in the practice of the european court of human rights - Човган, В. О. (Problems of legality, 2013)
The article is dedicated to the research of the standards of prisoner’s rights restrictions. In this context the question of the relevant practice of European court of human rights is analyzed.